P178 Development and implementation of a novel centralised virtual pulmonary rehabilitation service across an integrated care system. (11th November 2022) - Brook, M; Crisp, P; Webster, N
Abstract : Introduction: Pulmonary rehabilitation (PR) is at the forefront of the NHS long term plan, due to its ability to improve quality of life, functional capacity, admission prevention, and self-efficacy in patients with long term respiratory conditions. Virtual PR (VPR) has been found to be feasible and has accelerated in use over the course of the covid-19 pandemic with face to face (F2F) PR capacity reducing due to loss of venues, shielding, and increasing demand. VPR can increase patient choice, accessibility, and reach patients groups that may not engage in traditional F2FPR. We looked at the feasibility and implementation of a centralised VPR service across an integrated care system (ICS), spanning a large geographical area, and multiple pulmonary rehab systems. Many boroughs within the ICS were running their own VPR service. It was decided that centralising the service would increase patient choice by offering a greater variety of class days and times, but also increase clinical capacity for services to restart F2F services. Methods: A host site was agreed, which then recruited one physiotherapist and two B4 therapy assistants to run VPR for the whole ICS. The referral process to the host site was agreed and a pilot trialled with one borough referring in, to identify any barriers prior to opening the referral pathway to the rest of the ICS. Barriers identified were information governance, reporting of outcome measures (including NACAP), and establishment of responsibility for the patient. Results: Here we present preliminary data from the initial 3 months after service launch. At the time of writing, 35 referrals have been received from 4 out of the 6 boroughs. Of the 35 referrals; 8 chose not to start the course, 3 enrolled but failed to complete the course, and 4 have completed. The remainder are in class or have their start date booked. Conclusions: We have shown that operationally, a centralised VPR service is feasible to run across a large geographical area with multiple different PR services. Further analysis should target how the service has impacted staffing capacities and wait times across the network, and uptake amongst underrepresented groups.